Pendekatan Hukum Islam Terhadap Perlindungan Warga Negara - Riska Bayu Ifannia; Habibah yusraini; M Farhan Maulana Nst; Krisnanto Rizki A; Aulia Pratama (Tabayyun : Journal Of Islamic Studies, 2024)
Protection of human rights for citizens has an important role in ensuring justice and peace in a country. This article reviews ideas about protecting citizens' rights in the context of law, religion and government. Also discussed is the role of the Prophet Muhammad SAW. as inspiration in strengthening normative values ​​towards those in power in government. Through a descriptive qualitative approach using data from library research, this article presents a comprehensive picture of the government's efforts to fulfill the rights of citizens, including in the context of deported workers. Efforts to safeguard and defend individual and public rights, as directed by the Al-Qur'an, explain the importance of fulfilling citizens' rights as part of the government's responsibility.